MEMPERKUAT EKOSOSIAL UNTUK MENCEGAH DAMPAK BANJIR DI MALANG - Ihwan, Achmad Sutan (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2023)
This article discusses the importance of strengthening the ecosocial concept to prevent and reduce the impact of flooding in the Bandulan area, Malang. The Bandulan area, Malang often experiences floods. To find out the consequences and impacts of floods, we conducted observations and interviews with local residents. Through these observations and interviews, it is known that flooding occurs due to high rainfall, a lot of scattered garbage, and an ineffective drainage system. Meanwhile, the impact of floods includes damage to infrastructure, disruption of community activities, loss of property, and even risks to the safety of residents' lives. In this article, we propose an ecosocial approach that involves the interaction between ecological and social aspects to deal with the problem of flooding. This approach recognizes that solutions to flooding problems cannot rely solely on technical efforts, but also pay attention to human relationships with the surrounding natural environment. Measures such as increased public awareness, restoration of natural ecosystems, and sustainable urban planning can help achieve these goals. Hopefully, this article can provide useful insights and recommendations for the government, community, and other related parties in dealing with flood problems in the Malang Bandulan area.